Design and testing of a productivity based metal furring system for flat ceiling finishes - Decena, Johnlerry A.
Construction activities that experienced significant changes in materials technology have also experienced substantially greater long-term improvements in both their labor and partial factor productivity (Goodrum, et al., 2009). A material technology that has developed in the construction industry is the suspended ceiling systems. The Suspended ceiling system is a construction tool used to install architectural ceilings and to conceal utilities in the plenum. The metal furring system is composed of a galvanized grid system designed for the purpose of single or multilayer plasterboard screw fixed on the underside. Traditional systems comprise of primary channel supports to which the metal furring bar is clipped. Suspended ceiling installation is classified under finishing works. Finishing works refers to the treatment of walls, floors and ceilings (CSI MasterFormat, 2014). Finishing works is a major work package that is last to be implemented and is thus affected by the most number of probable lag times. These lag times could affect the time originally allotted for doing finishing works. Finishing activities are also dependent on the schedule of electrical and mechanical (E&M) services installation. By improving the speed of ceiling in stallation and by allowing simultaneous installation with E&M services, there could be an expected decrease in the time required for finishing works. The objective this study is to design an alternative metal furring system that would potentially enable faster and simultaneous installation with E&M works. The study will also evaluate if faster and simultaneous installation is possible. And based on the evaluation, to recommend design improvements to further increase productivity. The proposed ceiling system was conceptualized based on design objectives. These design objectives were extracted from literature review that focused on finding design features that would allow faster and simultaneous installation. The design objectives were used in order to conceptualize the scheme and method of installation of the proposed ceiling system. The component parts of the proposed system were dimensioned based on ergonomics analysis. The scheme of the proposed system was then designed for strength and serviceability. The design testing and assessment stage evaluated whether or not the proposed ceiling system was able to meet the study's objectives of faster and simultaneous installation. The design of the proposed system was assessed for the potential of increased productivity based on the improved design features. A time study was conducted in order to quantify the increase in productivity by comparing standard times of installation of the conventional and proposed system. Adequacy in design in terms of strength and serviceability was also analyzed using STAAD software. The predetermined motion time study indicates that the conventional metal furring system could still be in stalled faster than the proposed system. The comparison is based on the core motions of both installation processes. Deficiencies in the design of the proposed system include the higher number of hanger assemblies installed, the height adjustment mechanism and the weight of the frame components. After considering the recommendations for redesign, the proposed ceiling system was found to have a productivity that is twice that of the conventional.